GURITA (CEPHALOPODA) DARI PERAIRAN SANGIHE, SULAWESI UTARA - Carolus P. Paruntu, dkk (EKOTON, 2014)
Four species of genera Octopus are described and ilustrated from Sangihe waters, northen Sulawesi. They are Octopus marginatus Taki 1964, Octopus cyanea Gray 1849, Octopus sp.1 dan Octopus sp.2.